Kepemimpinan Pemuda Kristen Di Era Digital: Tinjauan Teologis Atas Media Sosial Sebagai Ruang Formatif Karakter Dan Pelayanan - Paulus Kunto Baskoro; Anon Dwi Saputro (Sekolah Tinggi Teologi Kanaan Nusantara, 2026)
This research critically examines, from a theological perspective, how the concept of Christian leadership, historically rooted in the example of Jesus Christ's servanthood can be re-articulated within the context of contemporary Christian youth's social media practices. It proceeds from the premise that digital media is not a neutral vehicle but a formative space that shapes the identity and relationships of its users. This study engages in a dialogical examination of digital theology literature alongside contemporary social psychology research on the impact of social media on young people's well-being. Through literature review and theological methods, this research argues that digital leadership with integrity requires three things: critical awareness of the attention economy logic that shapes the architecture of digital platforms; a reaffirmation of theological identity that does not depend on algorithmic validation; and concrete practices that translate the values of service, authenticity, and love into everyday social media actions.AbstrakPenelitian ini mengkaji secara teologis-kritis bagaimana konsep kepemimpinan Kristen, yang secara historis berakar pada teladan pelayanan Yesus Kristus, dapat direartikulasikan dalam konteks praksis bermedia sosial pemuda Kristen kontemporer. Bertolak dari premis bahwa media digital sebagai ruang formatif yang membentuk identitas dan relasi penggunanya. Penelitian ini menelaah secara dialogis literatur teologi media digital (digital theology) dan kajian psikologi sosial kontemporer mengenai dampak media sosial terhadap kesejahteraan generasi muda. Melalui metode kajian literatur dan teologis, penelitian ini berargumen bahwa kepemimpinan digital yang berintegritas menuntut tiga hal: kesadaran kritis terhadap logika ekonomi perhatian (attention economy) yang membentuk arsitektur platform digital; penegasan ulang identitas teologis yang tidak bergantung pada validasi algoritmik; serta praksis konkret yang menerjemahkan nilai pelayanan, otentisitas, dan kasih ke dalam tindakan bermedia sosial sehari-hari.